Dynamic transcription profiles of “Qinguan” apple (Malus × domestica) leaves in response to Marssonina coronaria inoculation - Xu, Jianhua; Li, Miaomiao; Jiao, Peng; Tao, Hongxia; Wei, Ningning; Ma, Fengwang; Zhang, Junke (Frontiers in Plant Science, 2015)
Marssonina apple blotch, caused by the fungus Marssonina coronaria, is one of the most destructive apple diseases in China and East Asia. A better understanding of the plant’s response to fungi during pathogenesis is urgently needed to improve plant resistance and to breed resistant cultivars. To address this, the transcriptomes of ‘Qinguan’ (a cultivar with high resistance to M. coronaria) apple leaves were sequenced at 12, 24, 48 and 72 hours post-inoculation (hpi) with Marssonina coronaria. The comparative results showed that a total of 1956 genes were differentially expressed between the inoculated and control samples at the 4 time points. Gene ontology (GO) term enrichment analysis of differentially expressed genes (DEGs) revealed changes in cellular component, secondary metabolism including chalcone isomerase activity, phytoalexin biosynthetic process, anthocyanin-containing compound biosynthetic process, lignin biosynthetic process, positive regulation of flavonoid biosynthetic process; and molecular functions or biological processes related to the defense response, biotic stimulus response, wounding response and fungus response. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis showed that DEGs were significantly enriched in flavonoid biosynthesis, vitamin B6 metabolism, phenylpropanoid biosynthesis, and the stilbenoid, diarylheptanoid and gingerol biosynthesis pathways. Furthermore, the importance of changes in cellular components and partial polyphenol compounds when encountering M. coronaria are discussed.